Neuroblastoma Soft Tissue Metastasis in a 10-Month-Old Infant with a Right Thigh Mass - Shokouh Taghipour Zahir; Fateme Salemi (Case Reports in Medicine)
Background. Neuroblastoma is a solid tumor that occurs more frequently in pediatric populations. It may originate from any part of the sympathetic nervous system, but it most commonly arises from the paraspinal sympathetic ganglia in the abdomen or mediastinum. Local lymphadenopathy and distant metastasis to the central nervous system, orbit, and liver might be detected; however, it rarely includes soft tissue or musculoskeletal involvement. Case Report. Here, we report a 10-month-old infant presented with a right thigh mass with an otherwise benign physical exam and medical history. MRI of the lower extremities suggested tumoral infiltration in the soft tissue of both thighs, predominantly on the right side. Surgical pathology of the lesion confirmed neuroblastoma. A large subhepatic mass and paraaortic lymphadenopathy in the abdominal CT scan and metaiodobenzylguanidine scan findings favored primary abdominal neuroblastoma that had spread to lower extremities. The patient has been in remission since the completion of chemotherapy. Conclusion. Neuroblastoma should be considered in infants with an abnormal mass in extremities. Due to its aggressive nature, most patients struggle with distant and local tumor spread at diagnosis. Therefore, any abnormal signs and symptoms, especially in younger pediatrics, warrant immediate evaluation to avoid tumor expansion.